Pengaruh kualitas pelayanan, sanksi pajak dan kesadaran wajib pajak terhadap kepatuhan wajib pajak dalam membayar pajak kendaraan bermotor - Oktrivina, Amelia; Sinaga, Lazarus; Hayadi, Antariksa Fikri (Jurnal Akuntansi dan Manajemen, 2024)
This study investigates the impact of service quality, tax sanctions, and taxpayer awareness on motor vehicle taxpayers' compliance. Using a quantitative descriptive approach, a sample of 100 two-wheeled motor vehicle taxpayers from SAMSAT Cinere in 2023 was analyzed using SPSS 26 software. The hypothesis testing results indicate that service quality and taxpayer awareness positively influence compliance, suggesting that taxpayers generally feel more satisfied with the services provided and that increased awareness can motivate them to make timely payments. Conversely, tax sanctions hurt compliance, indicating that the current application of tax sanctions may be ineffective, warranting a reevaluation of the strategies employed. This research provides insights to improve taxpayer compliance.